Laboratory study on the suffusion behaviour of coarse gap-graded soils for use as potential upstream crack-fillers in zoned dams - Santos, R. N. C. (2015)
This paper presents an experimental study aiming at the evaluation the suffusion behaviour of coarse gap-graded soils, considered as potential upstream crack-fillers in zoned dams. Six granular gap-graded soils missing the medium-to-coarse sand fraction have been examined. Four soils have no fines, one has 5% of non-plastic fines, and one has 5% of clayey fines (with plasticity index of about 14%). The use of available methods to assess internal stability of soils suggests that the majority of the selected soils are highly susceptible to suffusion. Testing has been carried out in the Upward Flow (UF) seepage test. A cylindrical seepage cell is used to impose vertical flow, from the bottom to the top, along a soil specimen with 200 mm-diameter and 150 mm-thick. During an UF test, the hydraulic gradient in the soil specimen is slowly increased in steps. The observation of the erosion behaviour at the top surface of specimen, together with the evolution of the discharge flow rate, allows determining the hydraulic gradients causing initiation of erosion on top of the specimen and development of suffusion in the soil. A ‘sand boiling’ phenomenon has been observed in soils exhibiting suffusion, resulting in the deposition of the finer particles at the specimen surface. One may conclude that the lower the gradient associated to the onset of ‘sand boiling’ phenomenon, and the higher the amount of material deposited in the top of the specimen, the higher the likelihood of gap-graded soils to be effective acting as upstream crack-filler. Laboratory testing on soils with no fines clearly shows that the higher the content of the fine sand fraction the higher the amount of material deposited on top of the specimen, however, the higher the gradients associated to initiation of suffusion and development of 'sand boiling'. Whenever high hydraulic gradients are not likely to occur, the gap-graded soil with 5% of non-plastic fines should be more reliable at filling in cracks than the gap-graded soil with 5% of clayey fines.